2001
DOI: 10.1080/09540120020018206
|View full text |Cite
|
Sign up to set email alerts
|

The negotiation of sexual relationships among school pupils in south-western Uganda

Abstract: The objective of the study was to explore how school-going adolescents in south-western Uganda negotiate sexual relationships. Qualitative data were obtained from 15 boys and 15 girls (14-18 years old), during a series of role plays, focus group discussions and one-to-one interviews. A questionnaire was administered to 80 pupils (12-20 years old) from the same school. Most of the pupils were sexually active. Sexual relationships between boys and girls were mediated by peers. Boys initiated relationships. Excha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
134
2
11

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(159 citation statements)
references
References 5 publications
12
134
2
11
Order By: Relevance
“…Often referred to as transactional sex, it is a motive for women to have sex in situations where they might otherwise refrain (Hunter, 2002;Jewkes, Vundule et al, 2001;Kaufman & Stavrou, 2004;MacPhail & Campbell, 2001;Meekers & Calves, 1997;Nyanzi, Pool et al, 2001;Wood & Jewkes, 2001), and has been noted as a potential source of women's vulnerability to genderbased violence and sexual exploitation (Dunkle, Jewkes et al, 2004a;Luke, 2003;Nyanzi, Pool, & Kinsman, 2001;Wojcicki & Malala, 2001). Research in a number of sub-Saharan African contexts has conclusively demonstrated that exchange of sex for material resources is common practice, and that the vast majority of women who engage in such transactions do not identify as sex workers (Hunter, 2002;Leclerc-Madlala, 2003;Luke, 2003;MacPhail & Campbell, 2001;Matasha, Ntembelea et al, 1998;Nyanzi, Pool, & Kinsman, 2001;Nzyuko, Lurie et al, 1997;Silberschmidt & Rasch, 2001;Wojcicki & Malala, 2001;Wood & Jewkes, 2001). However, research on the origins and implications of this behaviour remains limited.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Often referred to as transactional sex, it is a motive for women to have sex in situations where they might otherwise refrain (Hunter, 2002;Jewkes, Vundule et al, 2001;Kaufman & Stavrou, 2004;MacPhail & Campbell, 2001;Meekers & Calves, 1997;Nyanzi, Pool et al, 2001;Wood & Jewkes, 2001), and has been noted as a potential source of women's vulnerability to genderbased violence and sexual exploitation (Dunkle, Jewkes et al, 2004a;Luke, 2003;Nyanzi, Pool, & Kinsman, 2001;Wojcicki & Malala, 2001). Research in a number of sub-Saharan African contexts has conclusively demonstrated that exchange of sex for material resources is common practice, and that the vast majority of women who engage in such transactions do not identify as sex workers (Hunter, 2002;Leclerc-Madlala, 2003;Luke, 2003;MacPhail & Campbell, 2001;Matasha, Ntembelea et al, 1998;Nyanzi, Pool, & Kinsman, 2001;Nzyuko, Lurie et al, 1997;Silberschmidt & Rasch, 2001;Wojcicki & Malala, 2001;Wood & Jewkes, 2001). However, research on the origins and implications of this behaviour remains limited.…”
Section: Introductionmentioning
confidence: 99%
“…Studies from across Africa report prevalence estimates for the exchange of sex by young women for money or gifts ranging from 5% to 78% (Luke, 2005a;Matasha, Ntembelea, Mayaud et al, 1998;Meekers & Calves, 1997;Nyanzi, Pool, & Kinsman, 2001;Nzyuko, Lurie, McFarland et al, 1997). In South Africa, a study by Jewkes et al in Cape Town found that 21.1% of pregnant and 18.8% of non-pregnant teenagers reported having sex for money or presents (Jewkes, Vundule, Maforah et al, 2001), while a more recent study of women attending antenatal clinics in Soweto found that 21.1% of participants reported having ever had sex with a non-primary male partner in exchange for material goods or money (Dunkle, Jewkes, Brown et al, 2004a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An analysis of national level Demographic and Health Survey data found that among sexuallyactive 15-19 year old girls, the percentage who had engaged in transactional sex in the last 12 months ranged from 2 percent in Niger to 14 percent in Benin among the nine West African countries examined and was 14 percent and 27 percent among sexually-active girls in Kenya and Zambia, respectively.8 In Uganda, 31 percent of 15-19 year old adolescents reported that they received money or gifts in exchange for sex at their last sexual encounter.4 ;7 A review of studies based mainly on sub-national data or specific population groups (e.g., secondary school students) found five percent of girls 12-17 years old in Cameroon; about two-thirds of 10-18 year old girls in Malawi and 85-90 percent of rural girls 12-20 years old in Uganda reported ever engaging in sexual relations in exchange for money or gifts. [10][11][12] As can be seen from the Ugandan statistics presented above, big discrepancies across surveys in the same country suggest that measuring the receipt of money or gifts for sex may be highly sensitive to the wording of the question or it may be more prevalent in some sub-populations than others within the same country. Furthermore, some argue that even at the levels transactional sex is being reported, it is an underestimate because of the narrow definition of transactional sex used in survey questions (frequently only asking about gifts and money given proximally to the sex act) and because of the disincentive to report exchange behaviors due to the universally high level of social stigma attached to prostitution.…”
Section: Introductionmentioning
confidence: 99%
“…5;12,33;34 Evidence also shows that receiving a gift does not guarantee a man sexual access. Nyanzi et al (2001) found that girls in Uganda are able to delay relations and thereby increase the size and frequency of gifts, possibly never coming through with the expected sexual intercourse. 12 "Detoothing" is a Ugandan term used by girls to mean getting as much financial reward from a man while successfully eluding sex.12 ; 35 Yet detoothing can end badly: Some studies have found that adolescents, including girls, felt that rape is an acceptable response by men to having been detoothed.12 ;36…”
Section: Introductionmentioning
confidence: 99%